Does hospital delay in appendectomy affect immediate surgical outcome in adults with acute appendicitis? - Dhital, Saroj Prasad; Koirala, Udaya; Karki, Kushal; Joshi, Bijendra Dhoj; Upadhyaya, Amit Mani (Journal of Kathmandu Medical College, 2017)
Background: Emergency appendectomy is the commonest emergency surgical procedure being performed for many years. Till now, the dictum is that it should be done as soon as possible from the onset of attack. Objectives: To evaluate immediate surgical outcome in cases undergone appendectomy after hospital delay of more than 12 hours duration compared with appendectomy done immediately within 12 hours of presentation. Methods: This is a retrospective study of 118 patients on whom appendectomies were done between 1st June 2008 to 31st August 2010. These patients were divided into two groups on the basis whether the appendectomy was done ≤ 12hours or >12 hours from the time of presentation in the hospital and intergroup comparison was made regarding length of hospital stay, rate of perforation and post operative complications. Results: A total of 118 patients were included in the study. Out of which 71(60.2%) were male and 47(39.8%) were female. Mean age of patients was 30.97 ± 12 years. Mean duration of hospital stay was 4.35 ± 1.75 days. In comparison of two groups of ≤ 12 hours or >12 hours from the time of presentation in the hospital, there were no statistically significant difference in length of hospital stay (4.29 vs 4.4 days, p=0.7), rate of perforation of appendix (9.25% vs 10.93%, p=0.3) and post-operative wound infection (16.66% vs 17.18%, p = 0.9). Conclusion: Delaying an appendectomy for a valid reason can be considered. Prospective trials are required to establish findings of this study. Journal of Kathmandu Medical College, Vol. 5, No. 4, Issue 18, Oct.-Dec., 2016, Page: 112-115